KOMPETENSI GURU DALAM MENGHADAPI TANTANGAN TEKNOLOGI DIGITAL - Elia, Sukma; Patimah, Siti; Bedi, Fisman; Mas Ayu, Sovia; Junaidah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The progress of the world of education cannot be separated from the role of teachers, therefore teachers must have competencies that meet national education standards. There are four competencies that a teacher must have, namely; pedagogical, personality, social, and professional competencies so that they can carry out their duties well and successfully. Currently, there are problems in the progress of the world of education. This problem is related to the era of the industrial revolution 4.0 and society 5.0. Where teachers must have the competence to face technological developments in order to educate students. Technology continues to change to become faster and more sophisticated, but currently there are still many teachers who are resistant to technological developments even though the world of education has transformed. This article examines and analyzes how relevant the four teacher competencies are in the era of the industrial revolution 4.0 and society 5.0. In this study, it is hoped that the four competencies can answer the industrial revolution 4.0 and society 5.0. The method used in this study is document analysis, by analyzing sources obtained from books and journals. The type of approach used by the researcher is a qualitative research approach which is a temporary study. From the results of this study, researchers can find out that the four teacher competencies are still relevant in the era of the industrial revolution 4.0 and society 5.0.